Ants (Hymenoptera: Formicidae) in hospital centers of Valle del Cauca as vectors of nosocomial pathogens - OLAYA-MÁSMELA, LUZ ADRIANA; CHACÓN DE ULLOA, PATRICIA; PAYÁN, ANDREY (Revista Colombiana de Entomología, 2005)
Ants and nosocomial pathogens carried by them were studied in health care centers at four localities in the department of Valle del Cauca: Cartago, Tuluá, Cali and Buenaventura. Seven species were found, of which Paratrechina longicornis and Tapinoma melanocephalum were the most frequently collected. Fourteen bacterial types were isolated; eight were found to be exclusively transported by four species of ants (T. melanocephalum, P. longicornis, Tetramorium bicarinatum y Monomorium pharaonis). The most virulent Gram-positive coccus was Staphylococcus aureus and the Gram-negative bacilli were Escherichia coli, Serratia marcescens, S. liquefasciens, Enterobacter agglomerans, and E. calcoaceticus. Staphylococcus sp. coagulasa (-) was the pathogen most commonly isolated from ants.